Workers, collectivism and the law : grappling with democracy - Carlson, Laura, 1961- (Elgar studies in law and society, 2018)
Workers, Collectivism and the Law offers a captivating historical account of worker democracy, from its beginnings in European guild systems to present-day labor unions, across the national legal systems of Germany, Sweden, the United Kingdom and the United States. Analysing these legal systems in light of a Habermasian concept of participatory democracy, Laura Carlson identifies ways to strengthen individual employee voice in claims against employers. Carlson highlights how employee voice and democracy, both collective and individual, assume different guises in each of these four labor law models. By tracing voice and democracy as components in the history of collective worker organizations, from guilds to journeymen associations to modern labor unions, Carlson demonstrates how history has shaped today's national labor law models. In the context of modern labor law's central focus on human rights, Carlson articulates the need for stronger legal defence of mechanisms of transparency and procedural due process, to enhance voice and democracy for union members in invoking rights and asserting protections for workers. This insightful book is indispensable reading for labor law academics and for those practicing in employment law, while those interested in the history of labor law will revel in its penetrating survey of the materials.